2021
DOI: 10.1186/s12889-021-10505-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of COVID-19 on youth sport in Australia and consequences for future participation and retention

Abstract: Background COVID-19 continues to represent the single biggest challenge to contemporary community sport globally. Compliance with social distancing policies, strict return-to-play protocols, and COVID-19 specific training has, perhaps, forever changed the way that children and young people engage in organised sport. Within this context, and while many children and families seek to re-engage with community sport, we (researchers and sport practitioners) have an obligation to ask questions about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 49 publications
2
81
0
Order By: Relevance
“…Pons et al [34], in a sample of young Spanish athletes, found that young people with worse training conditions suffered greater mental health problems. The relationship between sport, physical activity and mental health has been observed worldwide as a consequence of confinement conditions similar to those in Spain [48,[62][63][64][65]. This relationship between mental health and physical activity can work both ways, Chirico et al [59] observed, in a sample of Italian athletes during the COVID-19 confinement, that anxiety negatively influenced the intention to do physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…Pons et al [34], in a sample of young Spanish athletes, found that young people with worse training conditions suffered greater mental health problems. The relationship between sport, physical activity and mental health has been observed worldwide as a consequence of confinement conditions similar to those in Spain [48,[62][63][64][65]. This relationship between mental health and physical activity can work both ways, Chirico et al [59] observed, in a sample of Italian athletes during the COVID-19 confinement, that anxiety negatively influenced the intention to do physical activity.…”
Section: Discussionmentioning
confidence: 96%
“…Sport is an area heavily impacted by the pandemic due to closures or restrictions of training facilities and cancellations or postponement of sport events [22]. Detraining effects began after a few weeks [2], with a larger effect in older athletes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Physical distancing policies prevent the social experience that facilitated athletes' participation and retention in sports clubs in their communities. As a result, more attention is now required in the psychology of motivation, stress, interpersonal relationships, and psychological exhaustion [20].…”
Section: Covid-19 Contingency In Sportsmentioning
confidence: 99%
“…For elite athletes, the challenges are greater due to lack of sponsorship, financial support from federations, laboratories specialized in sports science, performance bonuses, among other things, so that it could even lead to a generation of athletes frustrated by physical, psychological, social and economic loss [20].…”
Section: Covid-19 Contingency In Sportsmentioning
confidence: 99%